Low complexity DCO-FBMC visible light communication system - Abdullah A. Qasim; M. F. L. Abdullah; Rahmat Bin Talib; Mohammed N. Nemah; Ahmed T. Hammoodi (Institute of Advanced Engineering and Science, 2020)
Filter Bank Multicarrier (FBMC) is a new waveform candidate in the visible light communication system (VLC). FBMC is a distinctive kind of multi-carrier modulation that can be regarded as an alternative to orthogonal frequency Division Multicarrier (OFDM) with CP (cyclic prefix). DCO-FBMC (DC-bias optical FBMC) has recently been used in VLC, because it overcomes all defects in the optical-OFDM system and has high spectral efficiency. but at the same time the traditional DCO-FBMC suffers from high complexity due to the use of Hermitian Symmetry for real signal, by using 2N-point subcarrier IFFT (Inverse Fast Fourier Transformer) in the modulator, and the output is N-point subcarrier FFT (Fast Fourier Transform) in the demodulator. In this paper, for the first time, the possibility of minimizing complexity and generating a real signal without the use of Hermitian Symmetry or any other technique has been verified. The proposed technology provides 50% of the size of the IFFT / FFT and this results in a significant reduction in power consumption and occupied chip area.